Financial Self-Efficacy, Lifestyle, and Peer Influence on Credit Decisions: The Mediating Role of Financial Control in Gen Z - Sapira, Bella; Juhari, Juhari; Suhardi, Suhardi; Makrus, Mohamad (Economic: Journal Economic and Business, 2025)
This study examines the influence of financial self-efficacy (FSE), hedonic lifestyle (HL), and peer influence (PI) on financial self-control (FSC), with financial control (FC) as a mediating variable among Generation Z. Amid the increasing complexity of financial decision-making in the digital age, this research highlights the interplay between psychological and social factors in shaping personal financial behavior. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 124 respondents aged 20–35 with financial decision-making experience. Results show that FSE has a significant positive impact on FC, and FC significantly affects FSC. However, FSE does not directly influence FSC but exerts a significant indirect effect through FC. HL does not directly impact FSC but negatively affects FC, indicating that a hedonistic lifestyle undermines practical financial control. While the indirect effect of HL on FSC is negative, it is statistically insignificant. Conversely, PI significantly influences both FC and FSC directly, although its mediation via FC is not significant. These findings underscore the critical mediating role of financial control. Practical financial education programs should address not only knowledge but also psychological confidence and social influences to enhance financial self-regulation in young adults.